Radiative transfer of Black turmeric and its interpretation of antimicrobial property by light scattering - Hussain, Farhana; Roy, Sanchita (European physical journal plus, 2024)
Light interacts with every matter according to the entity’s shape, size, and scattering properties. It employs the study of the intensity of scattered light as a function of angular distribution and conveys information regarding the morphology of the particles. The particles may range from nano to micrometer scale. We outline a method which uses static light scattering method to study the properties of antibacterial action of Black turmeric ( Curcuma caesia ) against bacterial cells, i.e., E. coli -ATCC 9637. The identification of Black turmeric (BT) with and without the inoculation of bacterial cells was performed by means of a He–Ne laser-based static light scattering (SLS) instrument which operated at incident probe wavelength of 632.8 nm. The samples displayed distinct angular behaviors for the d 11 normalized scattering parameters of the Mueller matrix depending on the unaided BT sample and that inoculated with E. coli . The sample of Black turmeric ( Curcuma caesia ) was chosen for our subject of investigation to study its antibacterial properties by both biochemical and light scattering methods. BT is a perennial herb with a bluish–black rhizome. It is a miracle herb with the highest curcumin content and has high medicinal value. The antibacterial activity of Black turmeric on the growth of E. coli -ATCC 9637 was carried out by using a biochemical method, namely, Agar well diffusion method . BT inhibited bacterial growth on the agar plate, leading to a noticeable inhibition zone, which confirmed the antibacterial action of BT. Investigation of the same samples was done by using SLS technique. The antibacterial activity was subsequently validated by the light scattering signals. This was undertaken to ascertain the scattering profile of the BT after the inoculation of BT with E. coli . The scattered light intensity was obtained for different angles over an angular range of 10°–170°. The changes in morphology of E. coli cells as a result of antibacterial action were recorded by light scattering investigations. The scattering signals of unaided BT and BT inoculated with E. coli displayed a similar trend line of scattering profiles; however, both the profiles significantly varied in their intensities. The scattering profiles of the BT samples have revealed their uniqueness in the unaided and inoculated forms with the bacterial strain. The samples displayed distinct scattering behaviors for the d 11 normalized scattering parameter of the Mueller matrix depending on the sizes of unaided BT and BT inoculated with E. coli . This ensured the use of a light scattering tool as an alternate means of studying the antimicrobial activity of BT without involving any invasive method. In this paper, we report the antimicrobial activity and health importance of BT by SLS for the first time. The experiments point out the possibility of achieving real-time identification of antibacterial action of BT against the selected microorganism by SLS. Graphical Abstract